2012
DOI: 10.1155/2012/873090
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Molecular Analysis of Some Commercial Samples of Chilli Peppers from Mexico

Abstract: The genus Capsicum provides antioxidant compounds, such as phenolics and carotenoids, into the diet. In Mexico, there is a wide diversity of species and varieties of chilli peppers, a fruit which has local cultural and gastronomic importance. In the present study, the relationship of the carotenoid and phenolic profiles with the RAPD fingerprint of three different commercial cultivars of chilli peppers of seven regions of Mexico was investigated. Through RAPD, the species of chilli were differentiated by means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 28 publications
4
16
0
Order By: Relevance
“…Phenolic compounds (gallic, protocatechuic, ferulic, o-coumaric, p -coumaric, sinapinic, trans-cinnamic and caffeic acids, quercetin, catechin, rutin, and vanillin) are present in commercial cultivars of chili peppers at different maturation stages (Troconis-Torres et al, 2012). In our study, the abundance of epicatechic, caffeic, and chlorogenic acids was increased in red fruits after the second application of both biostimulants.…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic compounds (gallic, protocatechuic, ferulic, o-coumaric, p -coumaric, sinapinic, trans-cinnamic and caffeic acids, quercetin, catechin, rutin, and vanillin) are present in commercial cultivars of chili peppers at different maturation stages (Troconis-Torres et al, 2012). In our study, the abundance of epicatechic, caffeic, and chlorogenic acids was increased in red fruits after the second application of both biostimulants.…”
Section: Discussionmentioning
confidence: 99%
“…In all the cultivars, with the exception of Aji Lemon Drop, Cayenne Purple, Fish, Jwala, Naga Morich and Tricolor Variegata, a decidedly larger size of fruits was found in 2018 in comparison with 2016. In 2016, the average weight of fruits of the tested genotypes ranged from 1.6 to 31.3 g, whilst in 2018 it was in the range 4.7-93.6 g. Troconis-Torres et al (2012) give the average weight of fruits for the Jalapeño as between 26 and 47 g, depending on the locality, and 8.1 g for the Habanero cultivar. Muñoz-Ramirez et al (2018) have stated the weight for 'TMSR' as 7.8 g, and for the 'Carolina Reaper' as 3.7 g. Bhuyan et al (2015) give a range of 3.5-10 g for 'Naga Morich'.…”
Section: Yield Parametersmentioning
confidence: 92%
“…PCA allows the reduction of the multi-variate matrix into the principal components to perform discrimination, which was realized by the second derivative of the spectra in the region 400-1,710. Different studies have reported the use of FT-IR-PCA as an efficient tool to evaluate the shelf life of cheese (Cattaneo et al, 2005), fresh-cut pineapples (Di Egidio et al, 2009), and to characterize other foods by geographic origin (Troconis et al, 2012).…”
Section: Ft-ir Analysis Of the Chili Sauce And Its Ingredientsmentioning
confidence: 99%